ستارة كسوة باب الكعبة المشرفة - Storage cabinet for the Noble Qur’an in Al-Rawdah | خزانة حفظ مصاحف الروضة الشريفة (2023)
Width 2.10 m Length 2.90 m The recorded texts: (We may see the turning of your face in the sky) (So let us give you a kiss that pleases you) (The Almighty said that it is from Solomon, and that it is in the name of God, the Most Gracious, the Most Merciful - and say, “My Lord, enter me into an entrance of sincerity and lead me out through an exit of truth, and grant me from You a supportive authority” (In the name of God, the Compassionate, the Most Merciful) ( those who are angry, nor those who go astray.) | العرض 2.10م الطول 2.90م النصوص المسجلة: (قد نرى تقلب وجهك في السماء) (فلنوليك قبلة ترضاها) (قال تعالى إنه من سليمان وإنه بسم الله الرحمن الرحيم – وقل ربي أدخلني مدخل صدق وأخرجني مخرج صدق واجعل لي من لدنك سلطاناً نصيراً) (بسم الله الرحمن الرحيم) (المغضوب عليهم ولا الضالين)